Advantages and disadvantages of blended learning in higher education - Khoshimova Mukhtaramkhon; Egamberdiev Jasur Jakhongirovich (Zien Journals, 2022)
The educational system at present is in a transition stage. To meet the challenges of expansion and for catering individuals need trying to adopt new technologies and exploring new paths to reach the goal of quality educational opportunities for all. At the same time due to various factors like deficient budgets, lack of facilities, advantages of face to face interaction, it is not completely ready to leave the traditional modes of knowledge transfer. The present paper tries to explain that how blended learning is an approach that needs to be adopted and it analyses the positive and negative sides of blended learning
Keywords: blended learning; technology; online learning; traditional learning